Increasing the Capacity of Azalea MSMEs through Logo Creation Training that Attracts Consumers: Peningkatan Kapasitas UMKM Azalea melalui Pelatihan Pembuatan Logo yang Menarik Konsumen - Herawaty, Vinola; Nainggolan, Juara S.; Sudibyo, Yvonne Augustine; Yanti, Harti Budi; Imani, Dzikrina Nuril (Yayasan Ahmar Cendekia Indonesia, 2025)
Azalea MSME, which focuses on local products in the form of handicrafts and snacks, faces challenges in building a strong and attractive brand identity. One of the main obstacles is the lack of understanding and skills in creating a representative business logo that matches the characteristics of the product. In fact, a good logo is an important element in branding and marketing strategies, especially in the digital era that demands strong and consistent visuals. This community service activity aims to empower Azalea MSME actors through logo creation training and an introduction to the basic principles of graphic design. The training includes theoretical material and direct practice using simple design applications. The implementation method includes the preparation stage, interactive training, evaluation of results, and publication of outputs. Lecturers, students, and alumni are actively involved in supporting this activity. With this training, Azalea MSME is able to increase product competitiveness by strengthening visual identity and more effective marketing strategies, so that it can expand market reach and create sustainable business growth.